Robotik Programlamanın Ön Lisans Öğrencilerinin Bilgi İşlemsel Düşünme Becerisi Gelişimine Etkisi. - KILIÇ, Servet (Afyon Kocatepe University Journal of Social Sciences / Afyon Kocatepe Üniversitesi Sosyal Bilimler Dergisi, 2022)
This research aims to examine the effect of robotics programming on the development of computational thinking skills of associate degree students. The research was conducted using a nested embedded mixed pattern. A total of 32 students, 28 males and 4 females, studying in the first year of the Vocational School Computer Programming Department, participated in the research. Students were given a total of 18 hours of robotic programming for 12 weeks synchronous in the online learning environment. Quantitative data was collected with computer thinking skills scale and qualitative data was collected with a semi-structured interview form. In the analysis of quantitative data, dependent sample t-Test and Wilcoxon signed rank test were used. Descriptive analysis method was used in the analysis of qualitative data. The findings obtained show that robotic programming significantly affects the development of students' computational thinking skills. In addition, while the difference between pretest and posttest scores is significant for creativity, critical thinking and problem solving skills, it is not significant in terms of algorithmic thinking and collaborative. While the students stated that robotic kits are a suitable tool for dealing with problems related to daily life, they stated that they play important roles in problem solving and creativity skills development. The results of this study are valuable in terms of both demonstrating the availability of robotic programming courses online and demonstrating the suitability of students for the development of computational thinking skills during the COVID-19 pandemic worldwide.